Adsorption of Malachite Green using Coconut Shell–Graphite Oxide (CS-GiO): Kinetic and Isotherm Studies - Hazzha Azzahra; Sultan Napoleon; Patricya Inggrid Wilhelmina Bolilanga; Rahmat Basuki; Gunaryo Gunaryo; Dea Dwi Ananda; Mayang Fauziah Putri Kuntjahjono; Robith Alzamzani; Nugroho Adi Sasongko; Akhmad Rifai; Nuha Nuha (Indonesian Scholar Society, 2026)
Malachite green (MG) is a toxic cationic dye commonly found in textile wastewater and poses serious environmental and health risks. In this study, coconut shell–derived graphene oxide (CS-GiO) was synthesized and evaluated as an adsorbent for the removal of MG from aqueous solutions. The material was prepared through carbonization of coconut shells followed by a modified Hummers method to oxidize coconut shell graphite (CS-Gi) into graphene oxide. Prior to oxidation, the carbonized material was purified using HF treatment. Structural characterization using FTIR confirmed the presence of oxygen-containing functional groups, indicating successful oxidation of CS-Gi into CS-GiO. Meanwhile, XRD analysis revealed the characteristic (002) diffraction plane and showed that CS-GiO exhibited lower crystallinity compared to CS-Gi due to the incorporation of oxygen functional groups that disrupted the original crystalline structure. Adsorption behavior was evaluated through isotherm and kinetic studies. The adsorption equilibrium was better described by the Langmuir isotherm model (R² = 0.9957) than the Freundlich model (R² = 0.9617), indicating monolayer adsorption on relatively homogeneous active sites. The maximum adsorption capacity (qm) was 35.95 mg g⁻¹, with a Langmuir constant (KL) of 37873.42 L mol⁻¹ and a separation factor (RL = 0.000995), confirming that the adsorption process is highly favorable. Kinetic analysis revealed that the adsorption follows the pseudo-second-order (PSO) model (R² = 0.99818), with a rate constant (k₂) of 813.63 g mol⁻¹ min⁻¹ and an equilibrium adsorption capacity of 0.000349 mol g⁻¹, suggesting a relatively rapid adsorption process. The adsorption mechanism is likely dominated by chemisorption, involving interactions between oxygen-containing functional groups on the CS-GiO surface and cationic MG molecules through electrostatic attraction, coordination interactions, and possible electron transfer. These findings demonstrate that CS-GiO derived from coconut shells is a promising adsorbent for the efficient removal of malachite green from aqueous systems.